2010
DOI: 10.1007/s00240-010-0308-z
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive percutaneous nephrolithotomy with multiple mini tracts in a single session in treating staghorn calculi

Abstract: There has been continuing controversy regarding multiple tracts in a percutaneous nephrolithotomy (PCNL) session that may bring more complications, especially severe bleeding need for transfusion, even nephrectomy. Little tracts may bring less trauma to renal parenchyma than standard PCNL tracts. We carried minimally invasive PCNL (MPCNL) in treating staghorn calculi with multiple 16Fr percutaneous tracts in a single session, in an attempt to get high stone free with little trauma, and compared the morbidity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
71
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 19 publications
5
71
1
2
Order By: Relevance
“…There are several publications on mini or micro PCNL for the treatment of kidney stones [22,23,24]. Our study reveals the clear advantage of PCNL for the treatment of kidney stones, but with considerably higher complication rates.…”
Section: Discussionmentioning
confidence: 62%
“…There are several publications on mini or micro PCNL for the treatment of kidney stones [22,23,24]. Our study reveals the clear advantage of PCNL for the treatment of kidney stones, but with considerably higher complication rates.…”
Section: Discussionmentioning
confidence: 62%
“…Nevertheless, it had similar complications yet a better stone clearance rate. 7 Aron and coworkers 17 also reported that PCNL monotherapy using multiple tracts is safe and effective and had an initial SFR of 84%. It could be the first-line option for staghorn renal calculi.…”
Section: Discussionmentioning
confidence: 97%
“…3 In 1998, we consolidated the procedure into a single stage and have since used this technique for all stones. [4][5][6][7] Large and complex stones constitute advanced calculus disease. The management strategy depends on the stone burden and their locations in the collecting system.…”
Section: Introductionmentioning
confidence: 99%
“…Advancements in MPCNL equipment and techniques have helped broaden the indication of MPCNL to any UTUL requiring PCNL intervention, as suggested by Guangzhou and colleagues [15]. Using multiple tracts, MPCNL allows for the removal of staghorn calculi or complex renal calculi [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, this forceful pulse flow raises a safety concern that the high intrapelvic pressure in MPCNL may cause backflow into the collecting system via vascular, lymphatic, and mesenchymal routes, and further subject patients to a higher risk of urosepsis [16]. In contrast to this concern, some suggest that MPCNL is safe, as the renal pelvic pressure remains lower than 30 mmHg, a pressure that usually leads to backflow.…”
Section: Discussionmentioning
confidence: 99%